Literature and Its Authors in the Interwar Lithuanian Radio Programs - Avižinienė, Birutė (Colloquia, 2021)
In the article, the author discusses the presentation of the Lithuanian literature by the State Radio Broadcast “Valstybės radiofonas” in 1926-1940. The author presents specific literary radio program genres (recitations, radio drama, lectures, and commemorations), identifies those Lithuanian authors who received the most attention, examines the image of the national writer and the function it played in radio lectures and programs, and the ways in which the writers themselves took part in the radio programs. Radio lectures dedicated to Lithuanian writers and literature and commemorations of the writers’ anniversaries had consistently strengthened the point of view of the Lithuanian Nationalist and Republican Union towards literature and attributed educational function to it. This function is particularly noticeable in the interpretations of the works and biographies of the three authors most often discussed on the air: Maironis, Kudirka, and Vaižgantas. These writers were treated as heroes, whose example was fostered to follow. The image of national writers was employed to create the personal cult of President Antanas Smetona. In accordance with this image, the political leader was presented as the successor of the activities of the writers’ who occupied a significant place in the society. In addition to this ideologized attitude to literature, another approach, which created preconditions for more independent literary processes and more critical reader, began to emerge. Interwar radio broadened the usual forms of literary communication and provided a platform for discussing literary news and a stage for the youngest writers who made their debut in the late 1920s and 1930s. Radio programs dedicated to literature (such as literary evenings and book reviews) demonstrate both the emerging reflection on literary processes and the more critical listener, and testify to the growing autonomy of literature.